Emotions involved in monetary gains and losses in young people: contribution to behavior economics - Madrigal Cortés, Abdel (2024)
Prospect theory predicts that people tend to make decisions based on a reference point and prefer safe options over taking risks. On the other hand, emotional states influence individuals’ decisions and their consequences of loss or gain, triggering negative or positive emotional reactions, respectively. The objective of the present study is to identify the emotions and their level of intensity involved in potential monetary gains and losses in young men and women from Mexico. Based on prospect theory and studies indicating the relationship between emotions and monetary gains and losses, the hypothesis was formulated that emotional intensity in losses would be evaluated higher compared to the emotional intensity experienced in gains. Additionally, the emotional intensity of losses would be higher in women than in men. The study included 257 young participants, 29.2 % men and 70.8 % women, aged between 17 and 30 years. The information was gathered over a period of three months. The instrument was administered to the participants through a digital form. Two hypothetical questions were asked regarding the emotions experienced in the face of a monetary loss and gain. The intensity with which men and women experienced these emotions was also assessed. For the analysis of the responses, the cores of the categories and their semantic distance were considered. The results show that in monetary losses, six categories of negative emotions were found: sadness, discomfort, frustration, anger, worry, and shame. On the other hand, in monetary gains, five categories of positive emotions were found: happiness, well-being, enthusiasm, satisfaction, and tranquility. The Gain/Loss ratio was calculated, identifying that the benefits are like the losses. The findings indicate differences between men and women in the intensity towards monetary losses, as the data showed that women scored higher in the intensity experienced in the face of an economic loss compared to men, corroborating the proposed hypothesis regarding the sensitivity experienced in losses. The score given for gains did not show significant differences. In conclusion, in the Mexican context, three emotional categories stand out for monetary gains (happiness, well-being, and enthusiasm) and two main emotional categories.